A Comparison of Two Online Learning Systems - Mark Nichols (Journal of Open, Flexible and Distance Learning, 2016)
Open Polytechnic is a single-mode provider of distance education with a rich history of print-based provision. Strategically, the institution is rapidly adopting an online-only approach, with some exceptions for programmes that require student contact. A recent and internal review of Moodle, the Open Polytechnic’s learning management system (LMS) indicated concern about the likely student experience for an online-only format, so an internal system called iQualify was developed. iQualify was developed specifically from a user-experience (UX) perspective to optimise the online-only learning experience. As part of the drive towards online-only education, Open Polytechnic courses are being purposefully redeveloped for iQualify, moving away from print-and textbook-based materials, and towards textbook-independent and online-only study. This article uses a UX perspective to compare student outcomes, high-level course evaluations, and student perceptions of the two approaches—Moodle, with print and textbook; and iQualify online-only. Findings indicate that while students tend to prefer printed materials, actual withdrawal and pass rates are not affected by an online-only approach. Respondents also indicated a significant preference for the new iQualify platform over Moodle, and openness to online-only study.